An 880 mW@15 K thermal coupled pulse tube cryocooler with active phase shifter. Issue 1 (1st May 2022) - Yin, Wang; Liu, Shaoshuai; Wu, Yinong; Jiang, Zhenhua; Ding, Lei; Song, Jiantang
Abstract: A two-stage Stirling-type pulse tube cryocooler (SPTC) operating in 15 K is developed in our lab for cooling infrared detectors and precooling helium JT cryocooler. For easy adjustment, the driven compressor of the SPTC is designed as two independent linear compressors. The second stage cold finger uses an active warm displacer (AWD) as phase shifter to maximize the cooling performance. The variation of pre-cooling temperature and swept volume of the AWD will influence the cooling capacity of the SPTC. The cooling performance are experimentally tested and analyzed. With the pre-cooling temperature of 80 K, the second stage cold finger can obtain 470 mW at cooling temperature of 15 K with a total electric input power of 363 W. It can also obtain 880 mW at cooling temperature of 15 K with full input power of 527 W. A no-load temperature of 9.9 K can be obtained with an electric power of 180 W and 170 W for first and second stage. The experimental results also show that there exists an optimal pre-cooling temperature and swept volume of the AWD to achieve the maximum cooling capacity for 20 K applications.